PARADIGMA BARU PERKOPERASIAN DI INDONESIA (ANALISIS UNDANG-UNDANG NOMOR 17 TAHUN 2012 TENTANG PERKOPERASIAN) - Abd. Rasyid R (Institut Agama Islam Negeri Bone, 2020)
AbstractThis paper is intended to describe the New Paradigm of Cooperatives in Indonesia with analysis on Law No.17 Year 2012 on Cooperatives. The study aims to analyze the Law No.17 Year 2012 on Cooperatives that have implication for the new paradigm of cooperatives in Indonesia. Law Number 17 Year 2012 on coopratives provides statement that the establishment of cooperatives should be legaly formal, and does not recognize any cooperatives that is not incorporated or has no deed of establishment. The position of the cooperatives organization that position of the board, so that the duties and authority of supervisors may propose candidates for the boards and may dismiss the board a while. This implies that the right to nominate members of the board are limited, and supervisor’s position becomes representative of all members of the cooperative. Similarly, administrators can be selected by non-members, this implies that the cooperative may be interfered by other parties who have no interest in the interests of all members of the cooperative, but the emphasis is on their own interests, to the detriment of member of the cooperative. Implications for capital in the form of the new Law on cooperatives in Indonesia is transformed into a cooperative business entity pools of capital, no longer based on a collection of people. Because the capital certificate does not become full rights to their owners, as it can only be fully refundable if there is a buy, despite having been declared himself resigns a member of the cooperative. Kata Kunci : Paradigma; Perkoperasian; Implikasi.